Analisis Rasio Profitabilitas untuk Mengukur Kinerja Keuangan PT WEHA Transportasi Indonesia Tbk Periode 2023-2025 - Fajar Dimas Saputra; Rama Nugraha Irawan Surayuda (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Bina Insani, 2025)
The growth of the transportation sector in Indonesia provides opportunities for companies such as PT WEHA Transportasi Indonesia Tbk. However, financial performance needs to be evaluated periodically given indications of declining net profit amidst increasing sales. This study was conducted with the aim of determining the company’s financial performance based on the level of effectiveness in generating profits through profitability ratio analysis. The research method applied was descriptive quantitative with financial report data for the period 2023–2025 sourced from the Indonesia Stock Exchange, then analyzed using the Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) ratios, and compared with the average land passenger transportation industry. The results showed that all three ratios have decreased consistently each year, indicating the company is in a growth trap phase due to swelling operational costs that are accelerating faster than sales growth. The company’s NPM and ROA were above the industry average throughout the period and are categorized as good, while ROE was categorized as good in 2023 and 2024 but less good in 2025 because it was below the industry average. It was concluded that the company needed to shift from an expansion strategy to operational consolidation through restructuring its capital allocation policy, implementing a moratorium on new fleet capital expenditures, and restructuring routes to restore profitability margins sustainably. Keywords: Financial Performance, Net Profit Margin, Profitability Ratio, Return on Assets, Return on Equity